DETERMINANTS OF ADOPTION OF IMPROVED CASSAVA VARIETIES AMONG FARMING HOUSEHOLDS IN OGUN STATE, NIGERIA - ADEKOYA, O. A.; ADEKOYA, O. A.; DIPEOLU, A. O.; ASHAOH, O. E.; ADEWUYI, S. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This paper examines the adoption of improved cassava varieties among farming households in Ogun State, Nigeria. Multi- stage sampling procedure was adopted to collect data from 216 cassava farming households in Odeda, Ifo, Yewa South and Imeko-Afon Local Government Areas with the aid of structured questionnaire. Both descriptive and quantitative methods were used in the analysis of the study data. While Logit model was used to determine the factors affecting adoption of improved cassava varieties, Tobit model was used to determine the factors affecting the ratio of land allocated to improved cassava varieties. Tobit regression results indicated that farmer's experience (p<0.0 l), farmer's education (p<0.05), household size (p<0.05) and extension contact (p<0.01) significantly influenced intensity of adoption of improved cassava varieties. It is therefore, recommended that the farming households should make use of improved cassava varieties, form an effective linkage with the extension services and endeavour to be an active member of farmer's association in their community